Manejo multidisciplinario: una propuesta para mejorar la calidad de vida del paciente oncológico en quimioterapia - Muñoz M., Isabel Margarita; Briceño R., Constanza; Figueroa M., Gastón (Revista Hospital Clínico Universidad de Chile, 2013)
Cancer is a disease that impairs health of those who suffer it, affecting their quality of life. Chemotherapy produces deterioration on functional capacity as a result of the effects of therapy. Particularly affected are those patients who have to be admitted to receive treatment, by the very effects of hospitalization and prolonged rest. The deterioration of functional capacity (quality of life indicator) is explained by the alteration of physical capacity and ability to perform activities of daily living (ADLs) in an independent fashion, constituent elements of functional capacity. Given the prevalence of this disease, and the disability associated with both the disease and treatment, it is necessary to incorporate into daily practice interventions to reduce the impact on functionality, favoring the dequate reintegration of the person into his or her environment. The aim of this review is to describe the mechanisms that alterfunctional capacity, and the effects of physical training programs, complementary therapies and multidimensional interventions on symptomatology, well-being and quality of life of cancer patients in medical treatment.